Developing a pilot curriculum to foster humanism among graduate medical trainees - Sarah K Dotters-Katz; Alice Chuang; Amy Weil; Jennifer O Howell (Wolters Kluwer Medknow Publications, 2018)
Background: Humanism is a central tenant of professionalism, a required competency for all residency programs. Yet, few residencies have formal curriculum for teaching this critical aspect of medicine. Instead, professionalism and humanism are often taught informally through role-modeling. With increased burnout, faculty professionalism may suffer and may compromise resident role-modeling. The objective of this study was to design a pilot curriculum to foster humanism in among residents and assess its ability to do so. Materials and Methods: Two-phase exploratory sequential mixed methods study. Phase 1: a qualitative analysis of residents' narratives regarding challenges to humanistic behavior, and identified themes of compassion, fatigue, communication challenges, and work-life balance. Themes used as needs assessment to build curriculum. Phase 2: three sessions with themes taken from faculty development course. Participants and controls completed baseline and 60-day follow-up questionnaires assessing burnout, compassion, satisfaction, and ability to practice psychological medicine. Phase one included Obstetrics/Gynecology and internal medicine residents. Phase two included residents from the above programs, who attended at least 2/3 interactive sessions designed to address the themes identified above. Results: Twelve participants began and ten completed curriculum (83%). The curriculum met course objectives and was well-received (4.8/5). Burnout decreased (−3.1 vs. 2.5, P = 0.048). A trend toward improved compassion (4.4 vs.−0.6, P = 0.096) for participants compared to controls was noted. Conclusion: A pilot humanism curriculum for residents was well-received. Participants showed decreased burnout and trended to improved compassion scores. Development and evaluation of an expanded curriculum would further explore feasibility and effectiveness of the intervention.